Sancțiunile legale pentru remedierea clauzelor cu caracter abuziv în contractile de credit bancar [Articol] - Grozavu, Mircea (CEP USM, 2020)
The present study has the aim to perform a brief analysis of the legal progress of the legal sanctions for the unfair terms in bank loan contracts, using the rulings of the national courts of the Republic of Moldova and Romania.
LEGAL SANCTIONS FOR UNFAIR CONTRACTUAL TERMS IN BANK LOAN CONTRACTS
Keywords: contract de credit bancar